Mosaic Trisomy 18 in a Five-Month-Old Infant. (27th May 2013) - Fitas, Ana Laura; Paiva, Mafalda; Cordeiro, Ana Isabel; Nunes, Luís; Cordeiro-Ferreira, Gonçalo
Abstract : Individuals with mosaic trisomy 18, only approximately 5% of all trisomy 18 cases, carry both a trisomy 18 and an euploid cell line. Their clinical findings are highly variable, from the absence of dysmorphic features to the complete trisomy 18 syndrome. A five-month-old daughter of a 38-year-old mother, with vomiting and feeding problems, was referred to our department. She was undernourished and had axial hypotony and developmental delay, an irregular pattern of hypopigmentation on the right side of the abdomen, and moderate sagittal body asymmetry with left-side muscular hemihypotrophy. Mild craniofacial dysmorphy included dolichocephaly, frontal bossing, prominent occiput, long downslanting palpebral fissures, hypertelorism, and retrognathia. A complex heart defect with atrial and ventricular septal defects, pulmonary artery stenosis, and bicuspid aortic valve was identified. Cytogenetic analysis revealed mosaic trisomy 18 with trisomy in 90% of peripheral lymphocytes and 17% of skin fibroblasts. This case adds to our knowledge of the phenotypic spectrum and the natural history of mosaic trisomy 18 by adding a dysmorphic feature and a cardiac abnormality that, to the best of our knowledge, had not been previously described.